Laboratory mix design of asphalt mixture containing reclaimed material - Lo Presti, Davide; Khan, Rawid; Hassan, Norhidayah Abdul; Airey, Gordon; Collop, Andrew (Hindawi Publishing Corporation, 2014)
This paper presents a study on the production of asphalt test specimens in the laboratory containing reclaimed asphalt. The mixtures considered were stone mastic asphalt concrete mixtures containing up to 30% of reclaimed asphalt. Specimens were compacted to the reference density obtained from the Marshall mix design. Gyration compaction method was used for preparing specimens for the experimental programme, while coring and cutting methods and X-ray computed tomography (CT) were used to investigate the change in properties within the specimens and to validate the selected methodology.The study concluded that gyratory compaction is suitable to produce homogeneous test specimens also for mixtures containing high amount of reclaimed asphalt. Nevertheless, preliminary trials for each material are mandatory, as well as final coring and trimming of the specimens due to side effects.